The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fcimb.2021.622195
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of AmpC and Extended-Spectrum Beta-Lactamase Phenotypes in Escherichia coli and Salmonella From Alberta Broiler Chickens

Abstract: Horizontal gene transfer is an important mechanism which facilitates bacterial populations in overcoming antimicrobial treatment. In this study, a total of 120 Escherichia coli and 62 Salmonella enterica subsp. enterica isolates were isolated from broiler chicken farms in Alberta. Fourteen serovars were identified among Salmonella isolates. Thirty one percent of E. coli isolates (37/120) were multiclass drug resistant (resistant to ≥ 3 drug classes), while only about 16% of Salmonella isolates (10/62) were mul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…All tested E. coli isolates (100%) were positive for the int and qnr S genes. The high prevalence of the int 1 gene agrees with Ibrahim et al [ 37 ] and is lower than Tran et al [ 38 ], at 22.2%. The results of qnr S in the current study are lower than the result reported as 31.8% by Szmolka et al [ 39 ].…”
Section: Discussionsupporting
confidence: 90%
“…All tested E. coli isolates (100%) were positive for the int and qnr S genes. The high prevalence of the int 1 gene agrees with Ibrahim et al [ 37 ] and is lower than Tran et al [ 38 ], at 22.2%. The results of qnr S in the current study are lower than the result reported as 31.8% by Szmolka et al [ 39 ].…”
Section: Discussionsupporting
confidence: 90%
“…The detection of these genes was not surprising, as they have been reported in seafood products in Japan [35] and other countries [36][37][38]. Recently, the molecular characterization of ESBL-producing Enterobacterales with a wide range of drug resistance was retrieved from marine fish [38], chicken, and chicken meat [13,39,40], suggesting a wide distribution of ESBLs. These genes were commonly identified, possibly because of plasmid transfer mechanisms, which play an important role in the rapid dissemination of mobile genetic elements, not only in humans and animals but also within the aquatic environment.…”
Section: Discussionmentioning
confidence: 81%
“…Plasmid conjugation was performed between 48 ESBL-producing isolates harboring ESBL and spv genes, and E. coli J53 AZ r using the broth method [23]. The transconjugant was selected on Trypsin soybean agar medium supplemented with ampicillin (100 µg/mL) and sodium azide (200 µg/mL), and the positive transconjugant was further confirmed by the antimicrobial susceptibility test and PCR.…”
Section: Plasmid Conjugationmentioning
confidence: 99%